Upregulation of histone H3K9 methylation in fetal endothelial cells from preeclamptic pregnancies. Issue 3 (23rd July 2020) - Sheng, Wenji; Gu, Yang; Chu, Xiaodan; Morgan, John A.; Cooper, Danielle B.; Lewis, David F.; McCathran, Charles E.; Wang, Yuping
Abstract: Adverse intrauterine environment has been considered a predisposing factor for fetal programming in preeclampsia. Using human umbilical vein endothelial cells (HUVECs), we specifically explored if aberrant histone methylation occurs in fetal endothelial cells in preeclampsia. Strikingly, we found that increased di‐, and tri‐methylation of histone H3 lysine 9 (H3K9me2 and H3K9me3) expression were associated with upregulation of methyltransferase G9a and downregulation of endothelial nitric oxide synthase and CuZn‐SOD expression in preeclamptic HUVECs. We further demonstrated that hypoxia‐induced hypermethylation of H3K9 and reduced CuZn‐SOD expression mimicked what were seen in preeclamptic HUVECs and inhibition of G9a could attenuate these hypoxia‐induced adverse events. Our study was the first to identify hypermethylation status in fetal endothelial cells in preeclampsia, which provides plausible evidence that increased oxidative stress in the intrauterine environment is likely a mechanism to induce aberrant histone modification in fetal endothelial cells which may have a significant impact on fetal programming in preeclampsia. Abstract : This study found that the downregulation of CuZn‐SOD expression is associated with the upregulation of H3K9me2/3 and methyltransferase G9a expression in fetal endothelial cells from preeclamptic placentas. These results provide plausible evidence that aberrant histone modification occurs in fetal endothelial cells which may have a significant impact on fetal programming in preeclampsia.